Hypoallergenic unicompartmental knee arthroplasty and return to sport: comparison between Oxidized Zirconium and Titanium Niobium Nitride - Monti, Lorenzo; Franchi, Manuele; Ursino, Nicola; Mariani, Ilaria; Corona, Katia; Anghilieri, Filippo Maria; D'Ambrosi, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
Background: The present study aims to compare the rate of return to sports in patients who underwent surgery for mobile-bearing UKA with either hypoallergenic TiNbN or with oxidized zirconium alloy implants.Methods: The records of two consecutive cohorts for a total of 90 hypoallergenic implants were prospectively analysed. The first cohort consisted of 41 consecutive series of medial mobile-bearing hypoallergenic TiNbN UKA, whereas the second cohort consisted of 49 consecutive medial fixed-bearing hypoallergenic Uni Oxinium.The clinical evaluation involved evaluating each patient’s University of California, Los Angeles (UCLA) activity scoresand the High-Activity Arthroplasty Score(HAAS). Each patient was clinically evaluated on the day before surgery (T0), then after a minimum follow-up period of 12 months (T1), and finally after 24 months (T2).  Results:The only pre-operative difference between the two groups involved pre-operative BMI with significantly higher BMI in TiNbN Group (p